Phylogenomic Analysis Substantiates the gyrB Gene as a Powerful Molecular Marker to Efficiently Differentiate the Most Closely Related Genera Myxococcus, Corallococcus, and Pyxidicoccus - Liu, Yang; Pei, Tao; Yi, Shuoxing; Du, Juan; Zhang, Xianjiao; Deng, Xiaoqin; Yao, Qing; Deng, Ming-Rong; Zhu, Honghui (Frontiers in Microbiology, 2021)
Rapid and accurate strain identification of the most closely related genera Myxococcus, Corallococcus, and Pyxidicoccus can enhance the efficiency of the mining of novel secondary metabolites through dereplication. However, the commonly used 16S rRNA gene sequencing cannot accurately differentiate members of the three genera above, and the whole-genome sequencing is unable to rapidly and inexpensively provide species assignation toward a large number of isolates. To overcome the limitations, the gyrB gene was investigated as a candidate genetic marker for exploring the phylogenetic relationships of bacteria within the three genera and for developing the gyrB-based typing method. Here, the bacterial phylogeny and species affiliations of the three genera were determined based on the phylogenomic reconstruction and the analysis of digital DNA–DNA hybridization values among 90 genomes, further confirming nine novel taxa and assigning over one-third of genomes to defined species. The phylogenetic relationships of these strains based on the gyrB gene sequences were congruent with those based on their genome sequences, allowing the use of the gyrB gene as a molecular marker. The gyrB gene-specific primers for the PCR-amplification and sequencing of bacteria within the three genera were designed and validated for 31 isolates from our group collection. The gyrB-based taxonomic tool proved to be able to differentiate closely related isolates at the species level. Based on the newly proposed 98.6% identity threshold for the 966-bp gyrB gene and the phylogenetic inference, these isolates were assigned into two known species and eight additional putative new species. In summary, this report demonstrated that the gyrB gene is a powerful phylogenetic marker for taxonomy and phylogeny of bacteria within the closely related genera Myxococcus, Corallococcus, and Pyxidicoccus, particularly in the case of hundreds or thousands of isolates in environmental studies.